Approaches to promote handwashing and sanitation behaviour change in low‐ and middle‐income countries: a mixed method systematic review. Issue 1 (19th May 2017) - De Buck, Emmy; Van Remoortel, Hans; Hannes, Karin; Govender, Thashlin; Naidoo, Selvan; Avau, Bert; Veegaete, Axel Vande; Musekiwa, Alfred; Lutje, Vittoria; Cargo, Margaret; Mosler, Hans‐Joachim; Vandekerckhove, Philippe; et al.
Abstract : This Campbell Systematic Review examines the effectiveness of different approaches for promoting handwashing and sanitation behaviour change, and factors affecting implementation, in low and middle‐income countries. The review summarises evidence from 42 impact evaluations, and from 28 qualitative studies. Community‐based approaches which include a sanitation component can increase handwashing with soap at key times; use of latrines and safe disposal of faeces; and reduce the frequency of open defecation. Social marketing seems less effective. The approach mainly shows an effect on sanitation outcomes when interventions combine handwashing and sanitation components. Sanitation and hygiene messaging with a focus on handwashing with soap has an effect after the intervention has ended, but there is little impact on sanitation outcomes. However, these effects are not sustainable in the long term. Using elements of psychosocial theory in a small‐scale handwashing promotion intervention, or adding theory‐based elements such as infrastructure promotion or public commitment to an existing promotional approach, seem promising for handwashing with soap. None of the approaches described have consistent effects on behavioural factors such as knowledge, skills and attitude. There are no consistent effects on health. Plain language summary: Community‐based approaches are most effective in promoting changes in hygiene practices, but sustainability is a challenge: Community‐based approaches to promote handwashing and sanitation efforts seem to work better than social marketing, messaging and interventions based on psychosocial theory. Programs combining hygiene and sanitation measures appears to have a larger impact than either one alone. What is this review about?: Diarrhoeal diseases are very common causes of death in low and middle‐income countries. Improved sanitation and hygiene reduce diarrhoea, but adoption remains a challenge. This review assesses the evidence for two questions: (1) how effective are different approaches to promote handwashing and sanitation behaviour change; and (2) what factors influence the implementation of these approaches? What is the aim of this review?: This Campbell Systematic Review examines the effectiveness of different approaches for promoting handwashing and sanitation behaviour change, and factors affecting implementation, in low and middle‐income countries. The review summarises evidence from 42 impact evaluations, and from 28 qualitative studies. What studies are included?: Studies of effectiveness had to be impact evaluations using an experimental or quasi‐experimental design and analytical observational studies. Implementation studies used qualitative designs. Forty‐two quantitative studies and 28 qualitative studies met the inclusion criteria. The quantitative studies were conducted in LMICs worldwide, with the majority of the studies in South Asia and Sub‐Saharan Africa. What are the main findings of this review?: Community‐based approaches which include a sanitation component can increase handwashing with soap at key times; use of latrines and safe disposal of faeces; and reduce the frequency of open defecation. Social marketing seems less effective. The approach mainly shows an effect on sanitation outcomes when interventions combine handwashing and sanitation components. Sanitation and hygiene messaging with a focus on handwashing with soap has an effect after the intervention has ended, but there is little impact on sanitation outcomes. However, these effects are not sustainable in the long term. Using elements of psychosocial theory in a small‐scale handwashing promotion intervention, or adding theory‐based elements such as infrastructure promotion or public commitment to an existing promotional approach, seem promising for handwashing with soap. None of the approaches described have consistent effects on behavioural factors such as knowledge, skills and attitude. There are no consistent effects on health. What factors affect implementation? Implementation is affected by length of the intervention; visit frequency; use of short communication messages; availability of training materials; kindness, respect, status and accessibility of the implementer; recipient awareness about costs and benefits and their access to infrastructure and social capital. For community‐based approaches, involvement of the community, enthusiasm of community leaders, having a sense of ownership, the implementer being part of the community, gender of the implementer, trust, income generating activities, clear communication and developing a culture of cooperation facilitated implementation. For sanitation and hygiene messaging, text messages should be short and culturally appropriate, passive teaching methods in schools and reminders should be frequent and over a long period. Barriers include illiteracy and a lack of interest and involvement from the family in case of a school intervention. For the social marketing approach barriers were mainly about the use of sanitation loans such as lack of communication to latrine business owners about which area to cover, loan processing times and sanitation loans not reaching poor people. What do the findings of this review mean?: Promotional approaches aimed at handwashing and sanitation behaviour change can be effective in terms of handwashing with soap, latrine use, safe faeces disposal and open defecation. A combination of different promotional elements is probably the most effective strategy. Identifying and tackling the different barriers and facilitators that influence the implementation of these promotional approaches can increase effectiveness. An important implication for research is that there is a need for a more uniform method of measuring and reporting on handwashing, latrine use, safe faeces disposal, and open defecation. How up‐to‐date is this review?: The review authors searched for studies published until March 2016; this Campbell Systematic Review was published in May 2017. Executive summary/Abstract: BACKGROUND: Water and sanitation are at the very core of sustainable development, critical to the survival of people and the planet. The Sustainable Development Goal 6 (i.e. 'ensure availability and sustainable management of water and sanitation for all') addresses the issues relating to drinking water, sanitation and hygiene. It is unclear which Water, Sanitation and Hygiene (WASH) promotional approach is the most effective for sanitation and hygiene behaviour change, and other outcomes leading to behaviour change (e.g. learning outcomes) or longer term outcomes that follow from behaviour change (e.g. mortality, morbidity). OBJECTIVES: The overall goal of this systematic review is to show which promotional approaches are effective in changing handwashing and sanitation behaviour, and which implementation factors affect the success or failure of such interventions. This goal is achieved by answering two different review questions. Question 1 : What is the effectiveness of different approaches for promoting handwashing and sanitation behaviour change, in communities in low‐ and middle‐income countries? Question 2 : What factors influence the implementation of approaches to promote handwashing and sanitation behaviour change, in communities in low‐ and middle‐income countries? SEARCH METHODS: A comprehensive search was conducted to identify both published and unpublished studies. Using a sensitive search strategy, we searched the following databases from 1980 to March 2016: Medline (PubMed), Cochrane CENTRAL Issue 2, Applied Social Sciences index and abstracts (ASSIA, ProQuest), Global Health (CABI), EMBASE (OVID), PsycInfo (EBSCOHost), ERIC (EBSCOHost), Global Index Medicus, 3ie Impact Evaluation Database, International bibliography of the Social Sciences (IBSS, ProQuest), Sociological abstracts (ProQuest) and Social Sciences citation index (SSCI, Web of Science). To find unpublished material and relevant programme documents, we contacted various research groups and organizations and/or checked the relevant websites. SELECTION CRITERIA: Participants included both children and adults from low‐ and middle‐income countries (LMICs), as defined by the World Bank, at the time the intervention was implemented. Studies performed at an individual, household, school or community level were included, whereas studies conducted in institutional settings (e.g. hospitals) were excluded. The following promotional approaches or elements to promote handwashing, latrine use, safe faeces disposal, and to discourage open defecation (primary outcomes), were included: community‐based approaches, social marketing approaches, sanitation and hygiene messaging and elements of psychosocial theory. Secondary outcomes of interest were behavioural factors (knowledge, skills, attitude, norms, self‐regulation) and health outcomes (morbidity, mortality). For Question 1 (effectiveness of promotional approaches), we included impact evaluations using an experimental, quasi‐experimental design and observational analytical studies. To answer Question 2 (implementation aspects), all qualitative study designs addressing factors influencing implementation of the promotional approaches were considered for inclusion. This included, for example, grounded theory, case studies, phenomenological studies, ethnographic research, action research and thematic approaches to qualitative data analysis. DATA COLLECTION AND ANALYSIS: Study selection and data extraction (including risk of bias assessment) were performed independently by two reviewers, using EPPI‐Reviewer software. Study authors of all included papers were contacted by email (in July 2016) to ask for any relevant information, related to the population, intervention or outcomes, that was missing or not reported in the paper. Any disagreements between the two data extractors were resolved through discussion, or by consulting another review co‐author. The GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach was used to assess the overall quality/certainty of evidence from quantitative studies included in this review. The qualitative studies were assessed using the CASP (Critical Appraisal Skills Program) checklist. Evidence relating to Question 1 (effectiveness of promotional approaches) was synthesized in a quantitative way (meta‐analysis), where possible. RESULTS: Forty‐two quantitative studies and 28 qualitative studies met the inclusion criteria. The quantitative studies were conducted in LMICs worldwide, with the majority of the studies in South Asia and Sub‐Saharan Africa. Most quantitative studies (69%) were performed in a rural setting and only 14% of the studies took place in an urban setting (with an additional 10% in an "informal‐rural setting"). The effect of a promotional approach versus not using a promotional approach on sanitation and handwashing behaviour change, behavioural factors (knowledge, skills, attitude, norms and self‐regulation) and health‐related outcomes (morbidity and mortality), was studied in 34 different studies. In addition, 7 studies compared specific promotional approaches versus other promotional approaches, and one study compared two different communication strategies. All studies showed substantial variability in programme content, study types, outcome types, methods of outcome measurement and timing of measurement. Risk of bias assessments of included studies were influenced by unclear reporting or lack of reporting of key methodological aspects of the study design and process. Five percent of the experimental studies (n=2) had a high risk of selection bias, 40% had a high risk of detection bias (n=17), 28% had a high risk of attrition bias (n=12) and 48% had a high risk of reporting bias (n=20). Most quasi‐experimental and observational studies had bias in the selection of participants, some were at high risk of confounding, methods of outcome assessment were not comparable across intervention groups, and outcome assessors were aware of the interventions that the groups received. For the body of evidence, in most assessments, the certainty of evidence was considered as 'low' and in some cases 'moderate' or 'very low'. For the qualitative studies, an overall CASP score was given to the studies, and only 21% of the studies had a score less than 8/10. In studies with a lower score the relationship between researcher and participants was not adequately considered or ethical issues were not explicitly reported. We categorised the studies into 4 categories of promotional approaches or elements: (1) community‐based approaches, a promotional approach where there is typically community involvement and engagement, and shared decision‐making is part of the approach. All but one study in this category implemented a sanitation intervention, in some cases combined with a handwashing with soap and/or water supply/water quality component. (2) social marketing approaches, a promotional approach combining enterprise approaches with demand stimulation, and assuming that people both want and are able to change their behaviour. All but two studies in this category implemented a handwashing with soap intervention, in some cases combined with a sanitation and/or water supply/water quality component. (3) sanitation and hygiene messaging, is a predominantly directive educational approach, consisting mainly of one‐way communication, designed to help individuals and communities improve their health, by increasing their knowledge and/or skills. All but one study in this category implemented a handwashing with soap intervention, in some cases combined with a sanitation and/or water supply/water quality component. (4) elements of psychosocial theory, which are derived from a formal psychosocial theory and form the basis of the intervention. All but one study in this category implemented a handwashing‐only intervention, and one study implemented a combined handwashing and sanitation intervention. The most consistent results were obtained within the category of community‐based approaches, where at least a sanitation component was part of the programme. Working in a community‐based way may be effective in terms of handwashing with soap, and sanitation outcomes (latrine use, safe faeces disposal, and open defecation). Limited positive results on the knowledge of key handwashing times were found. Influencing factors that could play a specific role in the implementation of community‐based interventions are: a facilitator (e.g. health promoter, community leader) that is part of and representative of the community, the attitude of the implementer/facilitator, providing enough information, and creating a culture of cooperation. In addition, the gender of the facilitator seems to play an important role, since women prefer to discuss private issues with somebody of the same sex. The use of social marketing approaches seems to be less uniformly applicable, and mainly show an effect on sanitation outcomes when interventions have a combined handwashing and sanitation component. A specific barrier that could play a role in the implementation of social marketing interventions was the use of sanitation loans (slow and expensive process, not reaching the poor and people with lack of financial knowledge). Additional income generation would be an important facilitator for this type of approach. Sanitation and hygiene messaging, with a focus on handwashing with soap, seem to have an effect on handwashing programmes immediately after the intervention has ended. However, these effects are not sustainable in the long term. This type of promotional approach may make little or no difference to sanitation outcomes. With this approach it seems key that messages are delivered using active teaching methods and that messaging is innovative and culturally sensitive. In case of school level interventions with children, the duration of the intervention and involving the children's parents seem to be positive influencing factors. Using elements of psychosocial theory in a small‐scale handwashing promotion intervention, or adding theory‐based elements such as infrastructure promotion or public commitment to an existing promotional approach, seems promising for handwashing with soap. Finally, the methods used for communicating the content of a certain promotional approach, also play a role, and use of interpersonal communication was shown to be effective in certain circumstances. We only found a limited number of studies that incorporated a range of incentives (from soap bars to food or subsidies) into the promotional approach. One study reported promising results when using subsidies as part of the community‐based approach, but more research on the use of subsidies and incentives would be valuable. None of the promotional approaches described in the review showed consistent effects on behavioural factors such as knowledge, skills and attitude. Also no consistent effects on health were demonstrated. Facilitators which were relevant across different promotional approaches were: length of the approach, visit frequency, using short communication messages, availability of training materials, funding/resources and partnerships, kindness and respect of the implementer, accessibility of the implementer, and the implementer's authority/status; as well as, on the side of the recipient, awareness about costs and benefits, social capital, access to infrastructure and availability of space, and others showing the behaviour. AUTHORS' CONCLUSIONS: Implications for policy and practice. Based on our findings, promotional approaches aimed at handwashing and sanitation behaviour change can be effective in terms of handwashing with soap, latrine use, safe faeces disposal and open defecation. Findings from experimental, quasi‐experimental design and observational analytical studies show that a combination of different promotional elements is probably the most effective strategy. The recognition of different barriers and facilitators that influence the implementation of these promotional approaches may have a triggering effect on its effectiveness. Implications for research . An important implication of our work is that there is an urgent need to use a more uniform method of outcome measurement (type of outcomes, way of assessment, timing of assessment). This will facilitate making conclusions on the effects of promotional approaches in the future. In addition, it is important to further assess barriers and facilitators, identified in this review, alongside quantitative analyses of promotional approaches.